CRISPR/Cas9‐HPV‐liposome enhances antitumor immunity and treatment of HPV infection‐associated cervical cancer. Issue 1 (11th October 2022) - Zhen, Shuai; Qiang, Rong; Lu, Jiaojiao; Tuo, Xiaoqian; Yang, Xiling; Li, Xu
Abstract: Increasing evidence shows that human papillomavirus (HPV) E6/E7 deletion in cervical cancer cells may be related to the immunosuppressive tumor microenvironment and adverse reactions or resistance to immune checkpoint blockade. Here, we demonstrate that liposome delivery of CRISPR/cas9 can effectively knock out HPV, which, in turn, induces autophagy and triggers cell death‐related immune activation by releasing damage‐related molecular patterns. The results of in vivo experiments showed that HPV‐targeting guide RNA–liposomes could promote CD8+ T cell infiltration in tumor tissues; enhance the expression of proinflammatory cytokines, such as interleukin‐12, tumor necrosis factor‐α, and interferon‐γ, and reduce regulatory T cells and myeloid suppressor cells. The combination of HPV‐targeting guide RNA–liposomes with immune checkpoint inhibitors and antiprogrammed death‐1 antibodies produced highly effective antitumor effects. In addition, combination therapy induced immune memory in the cervical cancer model.